Generic reaction-diffusion model for transmission of mosquito-borne diseases: Results of simulation with actual cases - Kon, C.M.L.; Jane, Labadin (2016)
Mosquitoes can cause a lot of suffering to humans by transferring diseases. Malaria is a mosquito-borne disease caused by the parasite Plasmodium. It is an acute public health issue in many countries and can be fatal. Considering the similarity in the transmission of mosquito-borne diseases, a generic spatial-temporal model for transmission of multiple mosquito-borne diseases was formulated. The main concern here is whether the numerical results produced by this reaction-diffusion generic model are comparable with actual cases. Here, the actual notified weekly cases for 36 weeks, which is from week 39 in 2012 to week 22 in 2013, for four districts in Sarawak, Malaysia, namely Kapit, Song, Belaga and Marudi are compared with simulations of the generic model. The random movement of human and mosquito populations are taken into account. It is discovered that the numerical results are in good agreement to the actual malaria cases in the four districts.